Genre in Archaic and Classical Greek Poetry: Theories and Models Studies in Archaic and Classical Greek Song, Vol. 4 - Foster, Margaret; Kurke, Leslie; Weiss, Naomi (Mnemosyne, Supplements, 2019)
Genre in Archaic and Classical Greek Poetry brings together a range of innovative approaches to the question of genre, what it means, and how to think about it for Greek poetry from the eighth to the fourth centuries BCE. Readership: Students and scholars across the Humanities who are concerned with questions of genre and the history of lyric, and anyone interested in ancient Greek poetry.